Quality assurance guidelines for interstitial hyperthermia. (1st January 2019) - Dobšíček Trefná, H.; Schmidt, M.; van Rhoon, G. C.; Kok, H. P.; Gordeyev, S. S.; Lamprecht, U.; Marder, D.; Nadobny, J.; Ghadjar, P.; Abdel-Rahman, S.; Kukiełka, A. M.; Strnad, V.; et al.
Abstract: Quality assurance (QA) guidelines are essential to provide uniform execution of clinical hyperthermia treatments and trials. This document outlines the clinical and technical consequences of the specific properties of interstitial heat delivery and specifies recommendations for hyperthermia administration with interstitial techniques. Interstitial hyperthermia aims at tumor temperatures in the 40–44 °C range as an adjunct to radiation or chemotherapy. The clinical part of this document imparts specific clinical experience of interstitial heat delivery to various tumor sites as well as recommended interstitial hyperthermia workflow and procedures. The second part describes technical requirements for quality assurance of current interstitial heating equipment including electromagnetic (radiative and capacitive) and ultrasound heating techniques. Detailed instructions are provided on characterization and documentation of the performance of interstitial hyperthermia applicators to achieve reproducible hyperthermia treatments of uniform high quality. Output power and consequent temperature rise are the key parameters for characterization of applicator performance in these QA guidelines. These characteristics determine the specific maximum tumor size and depth that can be heated adequately. The guidelines were developed by the ESHO Technical Committee with participation of senior STM members and members of the Atzelsberg Circle.